Relationship of omission of adjuvant radiotherapy to outcomes of locoregional control and disease-free survival in patients with or without pCR after neoadjuvant chemotherapy for breast cancer: a meta-analysis on 3481 patients from the Gepar-trials - Krug, David; Lederer, Bianca; Debus, Jürgen; Blohmer, Jens-Uwe; Costa, Serban Dan; Eidtmann, Holger; Hanusch, Claus Alexander; Hilfrich, Jörn; Huober, Jens; Jackisch, Christian; Kümmel, Sherko; Paepke, Stefan; et al. (Journal of clinical oncology, 2017)
1008 Background: There is controversy whether the response to neoadjuvant chemotherapy should be incorporated into the decision-making process for adjuvant radiotherapy in breast cancer. Methods: We presenta pooled analysis of the randomized neoadjuvant trials GeparTrio, GeparQuattro and GeparQuinto including 3,481 patients with operable and non-operable breast cancer for which information on the use of radiotherapy (RT) was available. 94% received any RT. Locoregional recurrence was defined as a recurrence in the breast, at the chest wall or in the regional lymph nodes. Results: Patients in the RT-group were older and received more mastectomies. Their tumors were more likely to be HER2-positive and there was a higher rate of pathologic complete response (pCR, ypT0 ypN0). The overall risk of locoregional recurrence (LR) was 8.3% after a median follow-up of 55.9 months. RT conferred a significant benefit in terms of 5-year LR-free survival (LRFS, 90% vs. 81.5% without RT, logrank p < 0.001) and 5-year disease-free survival (DFS, 75.4% vs. 67.4%, logrank p < 0.001). The absolute advantage of RT regarding both LRFS and DFS was highest among patients with clinically positive lymph nodes at first diagnosis (HR 2.32, 95% CI 1.54-3.50; p < 0.001; HR 1.97, 95% CI 1.48-2.62; p < 0.001 respectively). In patients with pCR, the 5-yr LRFS was 95.7%% with RT vs 86.6% without RT (HR 3.32, 95% CI 1.00-11.08; p = 0.051) and 5-yr DFS was 86.9% and 56.1% (HR 3.52, 95% CI 1.82-6.83; p < 0.001). In patients without pCR, the LRFS was 88.6% with RT vs 80.7% without RT (HR 1.86, 95% CI 1.29-2.67; p < 0.001) and 5-yr DFS was 72.6% vs 65.7%; HR 1.39, 95% CI 1.07-1.81; p = 0.014). Multivariate analyses with adjustment for baseline parameters as well as for pathologic tumor stage and pCR confirmed RT as an independent prognostic factor for LRFS (HR 0.54, 95% CI 0.35-0.82; p = 0.004) and DFS (HR 0.69, 95% CI 0.51-0.93; p = 0.016). Conclusions: This retrospective analysis suggests thatpatients managed withoutRT after neoadjuvant chemotherapy for breast cancer have a significantly worse outcome even if they achieved a pCR.